Role of Bacteria in the Development of Colorectal Cancer - Thomas, Ryan M. (Clinics in Colon and Rectal Surgery, 2023)
Colorectal cancer (CRC) is the second leading cause of cancer-related death in the United States. Once limited to older populations, the incidence of CRC in patients under the age of 50 years is increasing and the etiology for this is uncertain. One hypothesis lies on the impact of the intestinal microbiome. The intestinal microbiome, composed primarily of bacteria but also viruses, fungi, and archaea, has been shown to regulate CRC development and progression both in vitro and in vivo. In this review, the role and intersection of the bacterial microbiome in various stages of clinical CRC development and management are discussed beginning with CRC screening. Various mechanisms whereby the microbiome has been shown to modulate CRC development including the influence of diet on the microbiome, bacterial-induced injury to the colonic epithelium, bacterial-produced toxins, and alteration of normal cancer immunosurveillance by the microbiome are discussed. Finally, the influence of microbiome on the response of CRC to treatment is discussed while highlighting ongoing clinical trials. The complexities of the microbiome and its role in CRC development and progression have become apparent and will require ongoing commitment to translate laboratory findings into meaningful clinical results that will aid more than 150,000 patients that develop CRC every year.
Keywords: microbiome; oncobiome; colorectal cancer; colon cancer; chemotherapy; immunotherapy